Zinc leaching behavior in semi-aerobic landfill. Issue 1 (2nd January 2019) - Hu, Lifang; Long, Yuyang
ABSTRACT: Municipal solid waste landfills require continuous monitoring because that the environmental change may trigger sudden release of heavy metals and need special care. In this research, three simulated landfills with different operation modes were used to investigate the behavior of Zn during the decomposition process. It is difficult to evaluate the effects of landfill operating modes on the release of heavy metals because the Zn concentration variation in leachate is similar in all three landfill types. However, the cumulative amount of Zn leached differed significantly with the landfill degradation degree. Zn can continuously leach from the traditional anaerobic landfill but relatively well retain in the semi-aerobic landfill. Leachate recirculation and air exposure not only promote the landfill stabilization process, but also obviously lower the risk of Zn pollution in the leachate by transforming it from unstable fractions to the more stable one, the residual fraction. Although heavy metal experiences vertical migration within the landfill, the transformation process retains it in the refuse and avoids its sudden release. The release of the most active fraction of Zn can be neglected during the rapid degradation stage and the most stable fraction of Zn can always be maintained at a positive level in all landfill modes tested.